The philosophical poetics of George Steiner. A rhetoric and dramatic reading of Antigones - Pego Puigbó, Armando (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
In the work of George Steiner Antigones plays a singular role. It is his book more philological in a classical sense, offering simultaneously a view over the 19th and 20th century philosophical reception of the Sophocles’ tragedy. This paper tries to analyze its general design and the disposition of its parts reflecting the philosophical interpretations which Steiner himself comments according to a rhetorical grammatical methodology. Having been built on a dramatic and musical pattern, its fields of analysis are those of translation, ontology and structural anthropology from Hegel and Hölderlin to Heideggeror Lévi-Strauss. The echoes and the parallelisms between its sections reflect, on the one hand, the dialectical irony of Sören Kierkegaard and, on the other hand, the attention to the details as studied byJacob Burckhardt or Aby Warburg